PENGARUH KUALITAS PELAKSANAAN PEMBELAJARAN, KETERSEDIAAN SARANA BELAJAR, DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR IPS SISWA PADA UPT SDI 117 KEPULAUAN SELAYAR - Alimuddin . (STKIP Pembangunan Indonesia Makassar, 2022)
This study aims to determine the effect of the quality of learning implementation on student social studies learning achievement at UPT SDI 117 Selayar Islands. 1) the influence of the availability of learning facilities on students' social studies learning achievement at UPT SDI 117 Selayar Islands. 2) the influence of student learning motivation on student social studies learning achievement at UPT SDI 117 Selayar Islands. 3) the influence of the quality of learning implementation, availability of learning facilities, and learning motivation simultaneously on student social studies learning achievement at UPT SDI 117 Selayar Islands. The type of research used is quantitative research. Quantitative research is a method used to answer research problems related to data in the form of numbers and statistical programs. The population in this study were all students of UPT SDI 117 Selayar Islands with a total sample of 17 people for class VI. Data collection techniques using questionnaires and documentation. The data analysis technique used descriptive analysis and multiple linear regression analysis. The results showed that 1) there was an influence between the quality of learning implementation on students' social studies learning achievement at UPT SDI 117. 2) there was an influence between the availability of learning facilities on students' social studies learning achievement at UPT SDI 117 Selayar islands according to the partial test which showed that 3) there is an influence of learning motivation on students' social studies learning achievement at UPT SDI 117 Selayar Islands. 4) there is an influence between the quality of learning implementation, availability of learning facilities, and learning motivation on students' social studies learning achievement at UPT SDI 117 Selayar Islands.Keywords: Learning, Learning Tools, Motivation, Achievement, Linear Regression